Cautious rebellion: A critical study of the Canadian historical play in English. - Hallett, David F. (University of Ottawa (Canada), 2000)
The Canadian historical play in English has long been subject to cursory, pejorative evaluation. Though a tradition of common practice has existed, almost unaltered, but still dynamic, since the earliest examples of the genre, there exists no articulated account of that tradition. Indications are that playwrights and critics alike have been largely unaware of the extent to which English-Canadian historical drama evinces a progress within a virtually paradigmatic structure. New developments in English-Canadian historiography suggest that a similar reconsideration of basic critical assumptions would benefit both the practice and the criticism of the English-Canadian history play. Building from a theoretical understanding founded in sociological and interdisciplinary cultural studies of the role of perception in "history" past and present, this study works to articulate a progress within a tradition, to set out the enduringly common features of English-Canadian historical drama. Through analytical commentary on twenty-eight plays, divided into five of the most common topical and thematic foci of the genre, this study establishes the roots of contemporary common practice in the earliest examples of the genre published in the late nineteenth-century, and traces the evolution of that practice through its most significant point of change midway through the twentieth century. The study argues that criticism to date has not fully comprehended the parameters within which the English-Canadian historical play has usually been written. English-Canadian historical playwrights are, in fact, paralleling (sometimes even anticipating) developments in Canadian historiography. Criticism of revisionist elements in the drama generally mistakes a strength for a weakness. Similarly, the omission of the non-Canadian historical subject from virtually all previous studies of the genre is an unnecessary limitation. Finally, and most importantly, the contemporary English-Canadian history play is not about history. Rather, it uses elements of history to critique and reconceive the present. Ironically, the contemporary English-Canadian historical play tends, in its reclamation of figures marginalized in the past, to make heroes out of individuals who were profoundly mistrustful of conventional discourses of heroism. If criticism of the genre has been imperfectly conceived, so too has practice of the form sometimes revealed its own ideological blind spots.
Keywords: Literature, Canadian (English).